WOMEN'S LEADERSHIP IN INDONESIA CONTEMPORARY FIQH PERSPECTIVE - Hamka, Hamka; Misbahuddin, Misbahuddin; Aidid, Hasyim; Satriani, Indra; Syamsuddin, Syamsuddin (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This paper describes the leadership of women in Indonesia in contemporary fiqh. The method used is literature and describes the main problems in the research. The sub-problems that are addressed are the role of women in the era of the Prophet and contemporary fiqh in women's leadership in Indonesia. This study found that the involvement of women in the time of the Prophet was not restricted in social aspects, attending lectures, discussion partners and so on. Reflecting that social involvement in the Sasulullah era was very open to women, it is not appropriate and fair if women are limited in their space of movement in social participation or career. The paradigm of women